1997
DOI: 10.1037/0022-3514.73.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and tacit inference.

Abstract: Tb judge another person's behavior, one often has to come to an understanding of what that behavior was in its detail. Five studies demonstrated that stereotypes influence the tacit inferences people make about the unspecified details and ambiguities of social behavior (e.g., what the behavior specifically was, what stimulus the individual reacted to, what caused the individual to act) and that these inferences occur when people encode the relevant information. One study found that participants who scored low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 55 publications
6
73
1
Order By: Relevance
“…The results found that asymmetric certainty was greater when answers came from stereotyped targets than when they came from nonstereotyped targets. This finding is consistent with a considerable amount of research showing that group stereotypes bias inferences from information about individual group members, so that the same information leads to stronger inferences of stereotype-consistent attributes when the information pertains to a member of a stereotyped group than a nonstereotyped group (e.g., Darley & Gross, 1983;Devine, 1989;Duncan, 1976;Dunning & Sherman, 1997;Kunda & Sherman-Williams, 1993).…”
Section: Discussionsupporting
confidence: 74%
“…The results found that asymmetric certainty was greater when answers came from stereotyped targets than when they came from nonstereotyped targets. This finding is consistent with a considerable amount of research showing that group stereotypes bias inferences from information about individual group members, so that the same information leads to stronger inferences of stereotype-consistent attributes when the information pertains to a member of a stereotyped group than a nonstereotyped group (e.g., Darley & Gross, 1983;Devine, 1989;Duncan, 1976;Dunning & Sherman, 1997;Kunda & Sherman-Williams, 1993).…”
Section: Discussionsupporting
confidence: 74%
“…Not only is sex the personal characteristic that provides the strongest basis of categorizing people, even when compared with race, age, and occupation (A. P. Fiske, Haslam, & Fiske, 1991;Stangor, Lynch, Duan, & Glass, 1992;van Knippenberg, van Twuyver, & Pepels, 1994), but also stereotypes about women and men are easily and automatically activated (Banaji & Hardin, 1996;Banaji, Hardin, & Rothman, 1993;Blair & Banaji, 1996). In addition, encoding processes advantage information that matches gender-stereotypical expectations (von Hippel, Sekaquaptewa, & Vargas, 1995), and spontaneous tacit inferences fill in unspecified details of male and female social behavior to be consistent with these expectations (Dunning & Sherman, 1997). The activation of beliefs about women and men by gender-related cues thus influences people to perceive women as communal but not very agentic and men as agentic but not very communal.…”
Section: Gender Roles: Expectations About the Actual And Ideal Behavimentioning
confidence: 99%
“…Variables that seem to qualify category activation in some studies turn out not to be in uential in others. For example, whereas some studies suggest that category activation is contingent upon prejudice levels (Lepore & Brown, 1997), Dunning and Sherman (1997) have demonstrated that implicit gender activation can be independent of people's level of sexism. Noting ambiguities of this kind, Bargh (1999) recently has provided a provocative review of the extant literature on the automaticity of category activation.…”
Section: Unresolved Issuesmentioning
confidence: 99%